2012
DOI: 10.3354/aei00047
|View full text |Cite
|
Sign up to set email alerts
|

Net-biting and escape behaviour in farmed Atlantic cod Gadus morhua: effects of feed stimulants and net traits

Abstract: Preventing farmed fish from escaping sea cages is a major challenge for developing sustainable aquaculture practices. In this study, the individual behaviour of Atlantic cod Gadus morhua to inspect and bite the net was investigated in 4 replicate multi-patch experiments, using underwater video techniques and behavioural event recording. The experimental system included a tank enclosure where cod were presented with 6 separate net panels: duplicate pairs of plain control nets and 2 different treatment panels. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…When cultured cod escape from net-pens, they interact with wild cod, and are subjected to the selective pressures of the natural environment (Moe et al 2007, Damsgård et al 2012, Zimmermann et al 2012. It is likely that the morphology developed by the cod in culture will be to some degree maladaptive in the wild, and thus any escapees will experience lower fitness than their wild counterparts, as has been seen in other species (Fleming et al 2000, McGinnity et al 2003, Meager et al 2010, Skaala et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…When cultured cod escape from net-pens, they interact with wild cod, and are subjected to the selective pressures of the natural environment (Moe et al 2007, Damsgård et al 2012, Zimmermann et al 2012. It is likely that the morphology developed by the cod in culture will be to some degree maladaptive in the wild, and thus any escapees will experience lower fitness than their wild counterparts, as has been seen in other species (Fleming et al 2000, McGinnity et al 2003, Meager et al 2010, Skaala et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the relatively well-studied Atlantic salmon Salmo salar, most escape events are related to structural failures of equipment, either due to human error or harsh weather conditions (Jensen et al 2010). In Atlantic cod Gadus morhua, the same problems exist, but exploratory behaviour and net biting are important additional drivers of escape events (Moe et al 2007, Damsgård et al 2012, Zimmermann et al 2012), contributing to 10-to 20-fold greater rates of escape than observed in salmonids (Moe et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Cod exhibit exploratory behaviors that increase the chance of fish detecting a hole and escaping (Hansen et al 2008). In addition, cod can bite the cage netting materials (Moe et al 2007, Damsgård et al 2012, and this biting behavior can weaken the net ). At present, direct evidence of the negative ecological impacts of escaped cod is sparse.…”
Section: Introductionmentioning
confidence: 99%